24. PLASMA PROCALCITONIN AND C-REACTIVE PROTEIN OF INPATIENTS WITH ACUTE EXACERBATIONS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE AT THE NATIONAL LUNG HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical characteristics as well as plasma levels of Procalcitonin (PCT) and C-reactive protein (CRP) of inpatients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD) at the National Lung Hospital.Subject and method: A cross-sectional study was conducted on 200 patients diagnosed with AECOPD and admitted to the National Lung Hospital from November 2023 to May 2024.Results: Most patients were male (91.5%), aged 60-79 years (76.0%). The highest mean FEV1 percentage was observed in GOLD 1 (91.67 ± 8.12) and the lowest in GOLD 4 (23.23 ± 4.59). Plasma CRP and PCT levels were highest in exacerbation grade I and GOLD 4, at 85.9 (96.61 ± 59.29) mg/L; 3.03 (9.54 ± 46.10) ng/mL and 92.1 (107.71 ± 53.03) mg/L; 4.06 (14.09 ± 67.53) ng/mL, respectively, and lowest in grade III and GOLD 1, at 56.95 (63.94 ± 36.22) mg/L; 0.25 (0.27 ± 0.20) ng/mL and 61.35 (64.23 ± 31.80) mg/L; 0.39 (0.29 ± 0.20) ng/mL, respectively, with statistical significance (p < 0.05).Conclusion: CRP and PCT are reliable biomarkers reflecting the severity and stages of AECOPD, effectively supporting diagnosis and treatment.
Keywords: acute exacerbations of chronic obstructive pulmonary disease (AECOPD); Procalcitonin (PCT) and C-reactive protein (CRP)